An Analysis of Digital Marketing Strategy for Syariah Maternity Services at YARSI Hospital - Pramita Ines Parmawati Raden Roro; Lia Gardenia Partakusuma; Enrico Adithya Rinaldi; Dicky Budiman; Sri Wuryanti; Hanny Handjadja Ronosulistyo (International Journal of Advanced Health Science and Technology, 2026)
The rapid expansion of digital technologies has transformed healthcare marketing; however, the adoption of Syariah-compliant maternity services remains relatively low despite high social media usage among executive patients in Indonesia. Limited evidence exists on how culturally and religiously aligned digital marketing strategies influence patient decision-making, particularly through Instagram. This study aims to analyze the effectiveness of Instagram-based digital marketing strategies in influencing executive patients’ intention to utilize Syariah maternity services at YARSI Hospital, Jakarta. A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 19 executive patients and analyzed using Spearman correlation to examine the relationship between five marketing dimensions informativeness, usefulness, authenticity, entertainment, and content variety and patient visit intention. Subsequently, qualitative data from 19 key informants, including patients, medical staff, and marketing personnel, were analyzed thematically to provide deeper insights into the quantitative findings. The results indicate that informativeness (r = 0.533; p = 0.019), usefulness (r = 0.492; p = 0.032), and authenticity (r = 0.482; p = 0.037) have significant positive effects on patient visit intention. In contrast, entertainment (r = –0.596; p = 0.007) and excessive content variety show negative associations. Qualitative findings reinforce that clear, practical, and culturally aligned content enhances trust and engagement, whereas low posting frequency and limited interactivity hinder marketing effectiveness. In conclusion, digital marketing strategies that prioritize informative, useful, and authentic content are more effective in promoting Syariah-compliant maternity services. Integrating cultural and religious values into digital communication is essential to strengthen patient trust and engagement. These findings provide practical implications for healthcare providers to optimize social media strategies in culturally sensitive contexts.